OPTIMALISASI UMKM RAJA BOLU - Irwandi, Irwandi; Samsir, Andi; Syachbrani, Warka; Ryketeng, Masdar; Oktaviyah, Nurafni (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2024)
MSMEs play an important role in creating jobs and contributing to the economy. Small and medium enterprises are used as a valuable opportunity to make money more profitably. Bolu is a very popular food in Indonesia. Steamed sponge cake has different variations, such as coconut milk, sugar, pandan leaves, and bananas. "Raja Bolu" is one of the MSMEs that needs to be optimized to be more advanced. By using a naturalistic method approach through a series of interviews, the information collected then leads to the development of conclusions and recommendations for utilizing digital marketing in revenue growth. Raja Bolu sales need to be optimized because they only use a banner. Raja Bolu has a distinctive taste but the food life is relatively short, no more than two nights because it does not use preservatives.